Feasibility of implementing same-day antiretroviral therapy initiation during routine care in Ekurhuleni District, South Africa: Retention and viral load suppression - Nolundi Mshweshwe-Pakela; Bhakti Hansoti; Tonderai Mabuto; Deanna Kerrigan; Griffiths Kubeka; Elizabeth Hahn; Salome Charalambous; Christopher J. Hoffmann (AOSIS, 2020)
Background: Same-day initiation (SDI) of antiretroviral therapy (ART) has been advocated as an approach to increase linkage to care and overall ART initiation. Clinical trials have demonstrated impressive benefits. However, questions regarding patient preparedness and retention in care remain for routine implementation of this approach. Objectives: In this study, we sought to describe SDI of ART during routine care delivery and compare time to ART initiation on longitudinal care outcomes. Method: We performed a retrospective chart review of 100 consecutive individuals, newly diagnosed with HIV, from 10 health facilities across Ekurhuleni, from January to July 2017. Records were reviewed for a period of 1 year post-diagnosis. Abstracted data included demographics, time to ART initiation, clinic visits and laboratory test results (including viral load testing). Results: A total of 993 patient records were reviewed, of which 826 were included in the analysis. The majority of patients (752, 91%) had ART initiation recorded, of which 654 (79%) had ART initiated within 30 days, and 224 (27%) had SDI. Uptake of SDI of ART was higher among women (36% vs. 10.4%; p 0.001) and in younger patients (33.7% in those 29 years; p 0.01). Retention in care at 6 months was achieved in 477 (58%) patients. Of those with 6-month viral loads, 350/430 (73%) had a viral load 400 c/m. Retention in care and viral suppression were similar among those with SDI of ART and later ART initiation. Conclusion: Same-day initiation of ART was successfully delivered with similar retention and viral load outcomes as subsequent initiation, providing re-assurance for scale-up of this strategy in routine care.